2003
DOI: 10.1159/000075201
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble Fas in Patients with Schistosomal Cor pulmonale

Abstract: Background: Schistosomal cor pulmonale is considered an important pathological condition in endemic areas. Few recent studies have reported the role of apoptosis in pulmonary hypertension. Objectives: The aim of this study was to assess serum levels of soluble Fas (sFas), an inhibitor of apoptosis, in patients with schistosomal cor pulmonale as compared to patients with cor pulmonale due to chronic obstructive pulmonary disease (COPD) and normal subjects. Methods: Serum sFas was assessed in 15 men with schisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…But until now there have been very few studies on the direct role of extrinsic apoptosis on schistosomiasis-induced pulmonary vascular disease. For example, soluble FAS is significantly higher in schistosomiasis pulmonary hypertension compared with those in patients with cor pulmonale resulting from chronic obstructive pulmonary disease 151 . Furthermore, soluble FAS (SFas) is shed from the cell surface through the action of certain enzymes like metalloproteinases 152 .…”
Section: Immunology and Inflammatory Role On The Pathogenesis Of Pulmmentioning
confidence: 97%
“…But until now there have been very few studies on the direct role of extrinsic apoptosis on schistosomiasis-induced pulmonary vascular disease. For example, soluble FAS is significantly higher in schistosomiasis pulmonary hypertension compared with those in patients with cor pulmonale resulting from chronic obstructive pulmonary disease 151 . Furthermore, soluble FAS (SFas) is shed from the cell surface through the action of certain enzymes like metalloproteinases 152 .…”
Section: Immunology and Inflammatory Role On The Pathogenesis Of Pulmmentioning
confidence: 97%
“…In patients with schistosomal pulmonary hypertension, serum levels of soluble Fas are significantly higher compared with patients with cor pulmonale resulting from chronic obstructive pulmonary disease. 40 This factor may contribute to the remodeling process of schistosomal pulmonary vascular disease.…”
Section: Immunological Modulation Of Schistosomiasis and Its Effect Omentioning
confidence: 99%
“…In the acute form of disease, patients present with shortness of breath, wheezing and dry cough associated with fever, myalgia, headache, hepatosplenomegaly and marked eosinophilia [60]. Salama et al [61] suggested that apoptosis of endothelial cells in the pulmonary vasculature also plays an important role in the pathogenesis of shistosomal cor pulmonale. Pulmonary involvement can occur in this phase, with ectopic migration of ova from the portal system to the pulmonary vascular bed.…”
Section: Schistosomiasismentioning
confidence: 99%